Disputing land: argumentative turn in local land policy conflict in Central Java, Indonesia - Laila Kholid Alfirdaus; Dzunuwwanus Ghulam Manar; Teguh Yuwono (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
This paper discusses the argumentative turn amongst farmers and the other different stakeholders in the case of land disputes, Kebumen, Central Java, Indonesia. While policy makers insisted that the land function conversion from agriculture and tourism to mining was needed to support local development as through the absorption of labors into employment sector, as well as to improve local people’s income, local farmers insisted that the conversion merely uprooting their ownership of land and let them back to periods where they were jobless and lack of source of income decades ago. This paper applied qualitative research supported with observation and interviews with parties involved in the case, to highlight the argumentative turn within land policy, which in the case of Kebumen leads to policy conflict. This paper identifies the elite-driven policy in the land dispute cases in Kebumen has led policy close to discussions with various stakeholders, which are necessary to be heard in the policy making. This finding highlights the idea that policy creates within itself politics that is in-line with the interest of the elites, and yet, resulted in the feedback loop, manifested through the strong resistance of the community.